CHANGES IN THE MORPHOLOGICAL AND MORPHOMETRIC PARAMETERS OF THE GASTRIC WALL IN POLYPRAGMASS WITH ANTI-INFLAMMATORY DRUGS - Tashmamatov B. N; DJumanova N.E (Scholar Express Journals, 2023)
Polypharmacy is becoming more common due to an aging population, an increase in the number of people with multiple diseases, and more disease recommendations. Although treating patients with complex medical problems with the right medications can improve clinical outcomes, quality of life, and life expectancy, polypharmacy is also associated with an increased risk of adverse drug reactions, some of which are serious enough to lead to hospitalization and even death. Therefore, it is critical to have systems in place to ensure that medications are only started when indicated, that patients are fully informed of the benefits and potential complications of treatment, and that patients are regularly reviewed to ensure compliance with their medication regimen
Keywords: Polypharmacy; multiple diseases; clinical outcomes